Exploring the impact of COVID-19 pandemic on nurses: A cross-sectional study on job burnout and quality of work life - Elahe Saleh; Mohamad Ezati Asar; Mohammad Reza Ghaneapur; Nayereh Harati Asl; Marzieh Belji Kangarlou (PLoS ONE, 2025)
Background The COVID-19 pandemic has posed unprecedented challenges for healthcare professionals, especially nurses, affecting their occupational health, burnout levels, and overall quality of working life. Limited research exists in the local context regarding these issues. Objectives To evaluate burnout and quality of working life among nurses during COVID-19, and to explore related factors such as exposure level, work shifts, and organizational conditions. Methods A cross-sectional study was conducted from January to March 2022 at Velayat Hospital in Damghan, Iran. All 217 active nurses were surveyed using the Maslach Burnout Inventory and Walton’s quality of working life questionnaire. Response rate was 58.5%. Data analysis was performed with SPSS. Results The nurses had an average age of 36.3 years; most were female (78.7%) and married (81.8%). The majority held bachelor’s degrees. Regarding quality of working life, 21.3% experienced poor quality, 71.3% moderate, and only 7.4% rated it as good. The lowest scoring domain was “fair and appropriate compensation,” while “development of human capabilities” scored highest. Over 70% experienced moderate to high emotional exhaustion, with higher exposure to COVID-19 correlating with increased burnout. Significant inverse relationships were found between emotional exhaustion and all quality of working life domains. Additionally, the number of shifts was associated with higher levels of depersonalization and perceptions of unfairness, safety, and growth opportunities. Nurses with moderate to severe exposure to COVID-19 reported higher burnout levels. Exposure to COVID-19 also negatively impacted perceptions of organizational legality and social environment. Conclusions The COVID-19 crisis has heightened occupational burnout and reduced quality of working life among nurses, risking the quality of healthcare services. Strategies such as workforce reorganization, improved working conditions, and mental health interventions are essential. Policymakers should prioritize supportive measures to enhance resilience and prepare for future crises.